Exploring the Medicine and Shaman Paradigm Shift for Game “Dukun Start-Up” Through Pixel Art Style - Faizal Akbar; Pratama Bayu (Gorga : Jurnal Seni Rupa, 2025)
This study addresses the lack of culturally meaningful visual representations in Indonesian indie games, with a particular focus on the implementation of the pixel art style for the game "Dukun Start-Up", which explores the culturally specific theme of shamanism (dukun). The study identifies a significant problem: despite the global popularity of pixel art, Indonesian developers rarely utilize it to convey in-depth cultural narratives, resulting in a gap between technical execution and cultural authenticity. This research is urgently needed to provide a methodological framework for integrating culturally specific assets into pixel art, moving beyond nostalgic aesthetics towards substantive cultural representations. Using a Practice-Based Research (PBR) methodology, the study follows a structured workflow aligned with industry-standard game development phases such as Pre-Production, Production, and Post-Production. Data collection included analyzing references from popular pixel art games, conducting in-depth research on shamanic practices and cultural symbolism, and holding collaborative brainstorming sessions to ideate and refine visual concepts. This study successfully designed and implemented a comprehensive set of pixel art assets, including characters, environments, and user interface elements, deeply embedded in Indonesian cultural motifs with a focus on shamanic symbolism. The findings demonstrate that pixel art, when applied thoughtfully, serves as a powerful medium for conveying cultural narratives, offering players an immersive experience that combines aesthetic appeal with educational value. This work provides practical insights for developers and communities interested in creating culturally themed games and highlights the effective integration of artistic practices and cultural research into game asset design.